A Novel Nipple Reconstruction Technique for Maintaining Nipple Projection: The Boomerang Flap - Kim, Young-Eun; Hong, Ki Yong; Minn, Kyung Won; Jin, Ung Sik (Archives of Plastic Surgery, 2016)
Nipple-areolar complex (NAC) reconstruction is the final step in the long journey of breast reconstruction for mastectomy patients. Successful NAC reconstruction depends on the use of appropriate surgical techniques that are simple and reliable. To date, numerous techniques have been used for nipple reconstruction, including contralateral nipple sharing and various local flaps. Recently, it has been common to utilize local flaps. However, the most common nipple reconstruction problem encountered with local flaps is the loss of nipple projection; there can be approximately 50% projection loss in reconstructed nipples over long-term follow-up. Several factors might contribute to nipple projection loss, and we tried to overcome these factors by performing nipple reconstructions using a boomerang flap technique, which is a modified C–V flap that utilizes the previous mastectomy scar to maintain long-term nipple projection.
Keywords: Breast reconstruction; Nipple reconstruction